2015
DOI: 10.1093/europace/euv067
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison between a fixed ‘2C3L’ approach vs. stepwise approach for catheter ablation of persistent atrial fibrillation

Abstract: For catheter ablation of persistent AF, the '2C3L' strategy is a fixed approach associated with clinical efficacy similar to that of the 'stepwise' approach but with less RF delivery, fewer X-ray exposure, and shorter procedural time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 27 publications
0
92
0
1
Order By: Relevance
“…Początkowo PVI zbadano u pacjentów z napadowym AF, ale wydaje się, że również w przetrwałym AF jest to metoda nie gorsza niż bardziej rozległa ablacja [729,735]. U pacjentów z przetrwałym AF wykonywano także bardziej rozległe zabiegi ablacji, ale nie ma wystarczających danych, by obecnie sformułować zalecenia dotyczące ich wykonywania [117,718,719,[735][736][737]. Rozległe zabiegi ablacji (wykraczające poza PVI) zawsze wymagają dłuższego czasu trwania zabiegu i większej ekspozycji na promieniowanie jonizujące, co potencjalnie stwarza zagrożenie dla pacjentów.…”
Section: Metody I Technologieunclassified
“…Początkowo PVI zbadano u pacjentów z napadowym AF, ale wydaje się, że również w przetrwałym AF jest to metoda nie gorsza niż bardziej rozległa ablacja [729,735]. U pacjentów z przetrwałym AF wykonywano także bardziej rozległe zabiegi ablacji, ale nie ma wystarczających danych, by obecnie sformułować zalecenia dotyczące ich wykonywania [117,718,719,[735][736][737]. Rozległe zabiegi ablacji (wykraczające poza PVI) zawsze wymagają dłuższego czasu trwania zabiegu i większej ekspozycji na promieniowanie jonizujące, co potencjalnie stwarza zagrożenie dla pacjentów.…”
Section: Metody I Technologieunclassified
“…30 In their study, the authors also included a cavotricuspid isthmus line in their lesion set. Their 12-month single-procedural success rates were 60% versus 67%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been reported that additional lesions after PVI increase the success rate of freedom from arrhythmia (9). A possible explanation for this result is that linear ablation will likely interrupt macro re-entrant circuit of AT (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the older age and higher prevalence of hypertension, diabetes and a higher left atrial mean size of our sample and, at least in part, by the use of a strict evaluation of atrial arrhythmia recurrences (48-hour Holter every month). Furthermore, two recent studies, that used PVI alone or together with extensive ablation in patients with persistent AF, have reported dissimilar findings suggesting no additional clinical benefits in patients undergoing a more extensive ablation (19,20). There are some potential explanations for such a discrepancy: the STAR AF II trial did not compare PVI to a stepwise ablation approach, and the outcome at the end of the first ablation was not sinus rhythm restoration and non-inducibility of further atrial arrhythmias (19).…”
Section: Discussionmentioning
confidence: 99%